Assessing the willingness of customers to share their data in exchange for the free use of mobile Apps - Carrapiço, Daniela Coelho (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence